Exploring Critical Perspectives of Toxic and Bad Leadership Through Film. (August 2015) - Edwards, Gareth; Schedlitzki, Doris; Ward, Jenna; Wood, Martin
The Problem: This article considers concepts of toxic and bad leadership from a critical, post-structuralist perspective and illustrates how this can be conveyed to management students through the use of film analysis. In response to the paucity of critical approaches within toxic and bad leadership studies, we suggest that film is a useful way of developing in-depth discussion in student and management groups to uncover underlying subtleties and complexity in leadership theory and practice. The Solution: We connect to film clips from Batman: The Dark Knight, and explain how this film is used with students and managers to illustrate the ambiguous nature of "good" and "bad" leadership and explore the fluid, shifting, and relational nature of these two concepts. We conclude that students and managers can recognize this more readily through viewing, discussing, and analyzing film clips such as the ones discussed herein. The Stakeholders: University lecturers and students, executive educators and managers, general human resource development (HRD) professionals